Building Public Trust Through Whistleblowing And Tax Law Enforcement: A Slippery Slope Framework Perspective - Abdiyah, Yuni Khoirotul; Tjaraka, Heru (Universitas Riau Kepulauan, 2025)
Tax compliance remains a persistent issue in Indonesia, especially at the regional level, where actual tax revenues still fall short of their potential. Despite tax revenue’s vital role in national development, many taxpayers do not file returns or fully comply with tax obligations. This problem is evident at the Regional Office of the Directorate General of Taxes (DGT) East Java I, which faces low compliance rates. Prior research suggests tax compliance depends not only on tax enforcement but also on public trust and participatory mechanisms such as whistleblowing. However, limited research has integrated these elements into a single framework. This study aims to examine the direct effects of whistleblowing and tax law enforcement on tax compliance and the mediating role of trust, based on the Slippery Slope Framework. A quantitative research design was employed, using primary data from questionnaires distributed to 400 individual taxpayers registered at DGT East Java I. Respondents were selected through purposive sampling to ensure direct tax experience. Findings show that whistleblowing significantly improves tax compliance, tax law enforcement negatively affects tax compliance, and trust fully mediates these relationships. The study contributes theoretically by extending the Slippery Slope Framework and practically by offering guidance for tax authorities to enhance whistleblowing systems, ensure transparent enforcement, and build public trust.